Effectiveness of Learning Through Online Technology in PAI Mapel at Madrasah Tsanawiyah: Efektivitas Pembelajaran Melalui Teknologi Daring Pada Mapel PAI di Madrasah Tsanawiyah - Ragil Aliet Sasongko; Ainun Nadlif (Universitas Muhammadiyah Sidoarjo, 2021)
This article was created for the results of research on the effectiveness of online learning in PAI subjects at MTsN Tembelang Jombang. Research Methods This article uses a qualitative method with a case study approach with the type of domain analysis with analytical techniques. Qualitative research is research conducted directly in the field to find all activities or direct phenomena that occur in an object under study. And for the type of analysis domain, it describes a broad and general analysis, but it is not detailed yet and is still comprehensive. The subjects in this study were class VII D students, which amounted to approximately 30 students, during this pandemic they carried out learning with whatsapp and google classroom media where the application requires a strong and stable signal so that learning can be carried out properly. Based on the discussion, it can be concluded that online online learning can be said to be quite effective.